Towards a more effective counter-drugs regime in the Indian Ocean. Issue 1 (2nd January 2016) - McLaughlin, Rob
ABSTRACT: Use of the Indian Ocean as a major drugs trafficking route – particularly for heroin originating in Afghanistan – poses a maritime security and a maritime law enforcement challenge. This article seeks to explore one dimension of this challenge – the lack of a 'legal finish' (such as prosecution) for the majority of drug seizures made within international waters in the Indian Ocean region. The article proposes three possible avenues towards improved outcomes: Formally combining the issues of terrorism and terrorist financing in Afghanistan with Indian Ocean heroin trafficking, in order to better leverage existing authorisations relating to the former; taking a more robust approach to asserting follow-on jurisdiction over unflagged vessels; and better utilisation of existing obligations, mechanisms and networks in order to achieve improved interdiction rates over flagged vessels.